농촌지역 아동복지 실태와 정책과제 - 이규천 (한국농촌경제연구원, 2008)
The purpose of this study was to find out why children who do not receive nurturing service exist in the rural areas and to depict the ways of institutional changes and policy improvements. We selected four counties for the case study and two counties for reference. The included are Youngdong, Buan, Sangju, and Youngyang as case study areas and Jinan and Hongcheon as reference areas. We conducted interviews with policy implementers, heads of nurturing facilities, parents, and social workers. Several problems were founded. The first problem lies in the shape of governance. Several ministries in the central government and several bureaus in local governments have implemented similar child welfare policies. This situation resulted in lowering specialty and policy ineffectiveness, the increase of administration costs, and differing the quality of welfare services. Secondly, rules regulating the operation of child welfare policy are more likely to benefit the urban areas than the rural ones such as the non-existence of kindergartens in several Myons, the limitation in local government's administration, administrative burden, and so on. Thirdly, there are children who do not receive policy benefits due to geographically remote residency, disability, and multi cultural families. Fourthly, some persons who are not farmer receive government support illegally. Also, some farmers who are self-nurturing their children and receive support spent it for other usage. Fifthly, some farmers cannot receive support because of ways of determining their income such as in calculating farming facilities. There are some policy tasks in order to improve the quality of nurturing. The first task is to return child welfare administration from local governments to the central government and to set up different welfare system for the rural areas. Secondly, it is very difficult to establish kindergarten in the rural areas because of the gradual decrease of the number of child and low possibility of establishing private kindergartens. However, in order that no one can be excluded from the policy benefits, government should establish new kindergarten for excluded children. Thirdly, a special consideration should be taken for disadvantaged groups such as multi cultural families and economically difficult families. Fourthly, government should make some solutions for recruiting teachers. In the long run, nurturing should be a kind of compulsory education. Also, government should consider a new child welfare system for rural areas different from the urban one. Lastly, an institutional re-arrangement is necessary: Ministry for Health, Welfare, and Family Affairs or Ministry of Education, Science and Technology. Researchers: Lee, Gyu-Cheon and Choi, Kyeong-Hwan Research period: 2008. 9. - 2008. 12. E-mail address: gclee@krei.re.kr